Measuring neutrino oscillation parameters using vμ disappearance in MINOS - Backhouse, C; Christopher Backhouse (2011)
MINOS is a long-baseline neutrino oscillation experiment. It consists of two large steel-scintillator tracking calorimeters. The near detector is situated at Fermilab, close to the production point of the NuMI muon-neutrino beam. The far detector is 735 km away, 716 m underground in the Soudan mine, Northern Minnesota. The primary purpose of the MINOS experiment is to make precise measurements of the "atmospheric" neutrino oscillation parameters (Δm2atm and sin22θatm). The oscillation signal consists of an energy-dependent deficit of vμ interactions in the far detector. The near detector is used to characterize the properties of the beam before oscillations develop. The two-detector design allows many potential sources of systematic error in the far detector to be mitigated by the near detector observations. This thesis describes the details of the vμ-disappearance analysis, and presents a new technique to estimate the hadronic energy of neutrino interactions. This estimator achieves a significant improvement in the energy resolution of the neutrino spectrum, and in the sensitivity of the neutrino oscillation fit. The systematic uncertainty on the hadronic energy scale was re-evaluated and found to be comparable to that of the energy estimator previously in use. The best-fit oscillation parameters of the vμ-disappearance analysis, incorporating this new estimator were: Δm2 = 2.32+0.12-0.08 x 10-3eV2 sin22θ > 0.90 (90% C.L.). A similar analysis, using data from a period of running where the NuMI beam was operated in a configuration producing a predominantly ̅vμ beam, yielded somewhat different best-fit parameters Δ̅m2 = (3.36+0.46-0.40 (stat.}) ± 0.06(syst.)) x 10-3eV2, sin22̅θ =0.86+0.11-0.12(stat.)± 0.01(syst.). The tension between these results is intriguing, and additional antineutrino data is currently being taken in order to further investigate this apparent discrepancy.